Coplanar Stripline-Fed Microstrip Yagi-Uda Antenna for ISM Band Application - Caliskan, Alper; Gunes, Filiz; Belen, Mehmet A.; Mahouti, Peyman; Demirel, Salih (IEEE, 2016)
In this paper, design and experimental results of a coplanar stripline fed Microstrip Yagi-Uda antenna are presented. The proposed antenna consists of a microstrip line to coplanar stripline transition, reflector microstrip patch, coplanar stripline-fed driver dipole, and three director microstrip patches on low-cost FR4 with the relative permittivity 4.4, thickness 1.58mm, loss tangent 0.025. The 10-dB bandwidth and gain are measured as 130 MHz at the center frequency of 2.45 GHz, 7.5 dBi.
Keywords: Yagi-Uda; Microstrip antenna; High gain; ISM band; ARRAY; Engineering; Telecommunications